Drip irrigation as a sustainable practice under saline shallow ground water conditions - Hanson, Blaine R., author; May, Don M., author; Hopmans, Jan, author; Simunek, Jirka, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Subsurface drainage systems cannot be used for addressing the saline, shallow ground water conditions of the San Joaquin Valley, California because no drainage water disposal facilities exist in the valley. Thus, the salinity/drainage problem of the valley must be addressed through improved irrigation practices such as converting to drip irrigation. Experiments in four commercial fields evaluated the effect of subsurface drip irrigation on processing tomato yield and quality, soil salinity, soil water content, and water table depth. The HYDRUS-2D computer simulation model evaluated leaching with subsurface drip irrigation under saline, shallow ground water conditions. Drip irrigation of processing tomatoes was highly profitable under these conditions compared to sprinkle irrigation. No trend in tomato yield was found with soil salinity levels. A water balance showed little or no field-wide leaching in the commercial fields, yet soil salinity data and computer modeling clearly showed localized leaching around the drip lines.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.